Analisis Sistem Pengendalian Internal dalam Meningkatkan Penjualan Sepeda Motor Honda di Dealer Astra Motor Bayah Banten - Muhammad Rifki Alfarisi; Darmo H Suwiryo; Sulaeman Sulaeman (AKUNTANSI 45, 2024)
Muhammad Rifki Alfarisi (2030611003) Muhammadiyah University of Sukabumi Analysis of Internal Control Systems in increasing Honda Motorcycle Sales at the Astra Motor Bayah Banten Dealer (Supervisor Dr. Darmo H Suwiryo, M.M. and Sulaeman, S.E., M.Si.) Every company needs to have an effective internal control system so that the company continues to develop and be stable. Internal control aims to provide security guarantees for the elements within the company. A good sales system is if internal control can be implemented well and controlled according to the criteria determined by management. Such as environmental control, supervision, information and communication, risk assessment, and also control activities. The type of research used by the author is a qualitative descriptive method, the data processed is data obtained from interviews and unstructured observations which will be analyzed qualitatively and described in descriptive form. The internal control system at the Astra Motor Bayah Banten Dealer has implemented and succeeded in the principles of internal control theory (COSO). However, the organizational structure at the Astra Motor Bayah Banten Dealer is not yet in accordance with the theory of (COSO) because the separation of duties is still not effective and there are no security personnel such as security.